Importance of Perception as a Parameter in University Rankings : A Critical Evaluation - Singh, Shashi; Singh, Ajay (Prabandhan: Indian Journal of Management, 2021)
Assigning ranks and grades (or stars) has been a common practice for ages to describe the characteristics of a product with the intention that it will significantly influence customers’ buying behavior. What started as a marketing tool to compare and show supremacy over competitors’ products, ranking and grading have now become institutionalized, involving many commercials at stake. Nowadays, ranking evaluation has altogether become separate diligence with stiff competition among different players. Such types of rankings and accreditations have also influenced the education sector. Though there are various international rankings (QS World University Rankings, Shanghai Ranking, Academic Ranking of World Universities, etc.) for the education sector, the Indian government also administrates its ranking system to bring in a sense of competition and performance reviews among academic institutions of India. With this thought, the National Institution Ranking Framework (NIRF), also popularly known as ‘India Rankings,’ was started in 2015. The NIRF rankings of higher education institutions (HEIs) offering engineering education were considered for the study. Perception as an evaluation indicator has always been debated for its validity in the finalization of such rankings. This paper attempted to scientifically study the influence that the parameter ‘perception’ contributes to the overall ranking of HEIs.